Horizontal crustal movements of the Red River Fault Zone in Vietnam from GPS Data (1994–2023) - Nguyen Viet, Thuan; Ngo Van, Liem; Phan Trong, Trinh; Nguyen Van, Huong; Tran Van, Phong; Nguyen Quang, Xuyen (Vietnam Journal of Earth Sciences, 2025)
This study analyzes horizontal crustal movements across the Red River Fault Zone (RRFZ), one of the major fault systems in northern Vietnam, using GNSS data collected over nearly 30 years (1994–2023). In the ITRF2008 reference frame, GNSS stations along the fault show an average East-Southeastward motion at a rate of approximately 32.65±0.4 mm/yr, consistent with the general movement of the South China (SC) block. A slight velocity difference of about 2.5 mm/yr between stations on the SC and Sundaland (SU) blocks indicates relatively stable regional tectonic conditions, although localized deformation persists. Relative velocity analysis between the two fault flanks reveals a right-lateral strike-slip rate of approximately 2±0.5 mm/yr, accompanied by a minor extensional component of about 1±0.3 mm/yr. These findings suggest a generally stable tectonic regime for the SC block, while also implying possible contributions from subsidiary fault structures or local deformation zones.